Ekonomi Islam Perspektif Ibnu Taimiyah - Andri Sutrisno (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2021)
Islam is revealed by Allah to regulate all forms of human behavior in dealing with other human beings to meet the needs of his life in the world. This includes the principles governing economic turnaround. In this case, one of the Islamic intellectuals, Ibn Taimiyah, has a concern in conceptualizing the economy through the approach of Islam. The study used descriptive qualitative research, in which researchers examined directly ibn taimiyah's books and several other supporting literature. In this study, researchers found that there are several concepts about islamic economy, namely fair price, market mechanism and price regulation that have some clear divisions in accordance with the concept of Islamic economy according to. Ibn Taymiyah.